Food, Food Stamps and Nutrition: An Evaluation of Methods of Recruitment and Instruction ; Public Communications Campaigns; Cartoons: When are they Effective; Science Meets the Press; Multimedia Instruction: High Learning, Low Cost - Debrah H. Jefferson; James W. King; Dot Sparer (Journal of Applied Communications, 1982)
Reviews of "Food, Food Stamps and Nutrition: An Evaluation of Methods of Recruitment and Instruction," by Richard A. Krueger and Bethaviva Cohen; Public Communication Campaigns, edited by Ronald E. Rice and William J. Paisley; "Cartoons: When are they Effective," by James M. Nehiley, James Stephens, and John Sutherland; "Science Meets the Press," by William E. Burrows; "Multimedia Instruction: High Learning, Low Cost," by Karin Kristiansson.